Escalonamento da síntese de zeólitas a partir de resíduos de carvão e da produção de alumínio - Hammerschmitt, Marta Eliza (2018)
Zeolites are aluminosilicates with wide use, which can be produced with alternative raw materials as waste, contributing to the reduction of possible environmental impacts and depletion of finite natural resources. In this study, environmental liabilities were characterized, such as fossil coal ash, and sludge resulting from the processing of aluminum used as an alternative source of aluminum and commercial sodium aluminate solution. The challenge of this work was to adapt the reactor (60 L) of low cost and to scale the synthesis of zeolites aiming the production in commercial scale. Due to the use of residues, the synthesis was divided into two stages, one of alkali extraction of silicon and aluminum and the other, hydrothermal gel-heating from the resulting aluminosilicate. Syntheses were carried out in bench and the best conditions were applied in making the scheduling of this synthesis on a pilot scale. Four route A, was prepared zeolite type 4A and FAU / 4A showed that high-purity and yield considering the mass of Al 98.84% and 70.91%, respectively. By route B, a mixture was produced 4A/FAU with the reuse of effluents generated in the process itself. These synthesized materials were characterized, their phases identified from the Bragg peaks and the Rietveld refinement (ZSc1.Ap). The high cation exchange capacity (CEC) of the Ca + 2 and Mg + 2 ions indicate the applicability of the zeolites produced.